2015
DOI: 10.1111/acem.12561
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Acute Stroke Using Quantified Brain Electrical Activity

Abstract: Objectives: Acute stroke is a leading cause of brain injury and death and requires rapid and accurate diagnosis. Noncontrast head computed tomography (CT) is the first line for diagnosis in the emergency department (ED). Complicating rapid triage are presenting conditions that clinically mimic stroke. There is an extensive literature reporting clinical utility of brain electrical activity in early diagnosis and management of acute stroke. However, existing technologies do not lend themselves to easily acquired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…ELECTRA-STROKE has yet to report on outcomes. There are alternative electrophysiological devices with intended application to the pre-hospital setting [79][80][81][82] but clinical publications are lacking. Other potential prehospital imaging technologies include Volumetric Integral Phase Shift Spectroscopy (VIPS) by Cerebrotech Medical Systems, Inc., which has been evaluated in hospital but not the pre-hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…ELECTRA-STROKE has yet to report on outcomes. There are alternative electrophysiological devices with intended application to the pre-hospital setting [79][80][81][82] but clinical publications are lacking. Other potential prehospital imaging technologies include Volumetric Integral Phase Shift Spectroscopy (VIPS) by Cerebrotech Medical Systems, Inc., which has been evaluated in hospital but not the pre-hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty percent of patients younger than 50 years suffering from a cerebrovascular event are migrainous (70), a percentage that rises to 29% in further younger patients (<35 years (71)). Furthermore, headache is reported in 13% of AIS with a negative brain CT scan in the acute phase (72), 27% of a large cohort of AIS (73), while it characterizes 28% of posterior circulation stroke according to a more recent article (74). Unfortunately, the available scientific works are not detailed enough to qualify the type of pain.…”
Section: Discussionmentioning
confidence: 99%
“…Such a thorough understanding also greatly reduces the difficulty of obtaining FDA approval, allowing for a shortened timeline to market. Notable medical devices that accurately predicted stroke in our review included EEG-based diagnosis with a maximum sensitivity of 91.7% for predicting a stroke, 23 microwave-based diagnosis with an AUC of 0.88 for differentiating ischemic stroke and ICH, 11 ultrasound with an AUC of 0.92, 27 VIPS with an AUC of 0.93, 8 and portable MRI with a diagnostic accuracy similar to that of traditional MRI. 28,29 In addition, current technologies require further innovation to accurately classify stroke subtypes while achieving acceptable scanning depths and volume sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The first study was published by Michelson et al in 2015 and demonstrated acute stroke diagnosis (ischemic and hemorrhagic) with high sensitivity (91.7%) and moderate specificity (50.4%). 23 Further experimentation by Gottlibe et al, Shreve et al, and Wilkinson et al confirmed the efficacy of EEG for ischemic stroke diagnosis using the changes in the revised brain symmetry index, alpha/delta frequency band ratios, and mixed delta/alpha ratio plus pairwise-derived brain symmetry index values, respectively. 10,13,24 These studies suggested that EEG may accurately predict acute stroke within 3 minutes.…”
Section: Stroke Diagnosis Using Eegmentioning
confidence: 92%